2008
DOI: 10.1111/j.1467-8624.2007.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Parental Differential Treatment: Parental and Contextual Factors During Middle Childhood

Abstract: The current study examined whether parental and contextual risk factors contribute to mothers' and fathers' differential treatment (MDT/FDT) when accounting for sibling dyad characteristics. Also explored was whether family type (single mothers vs. 2 parents) moderated the links between the parental and contextual correlates and MDT. One hundred and seventy-two families with older (M= 7.4 years) and younger (M= 5.2 years) siblings were studied. Parents and children reported about the parent-child relationship,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 69 publications
(76 reference statements)
4
82
1
Order By: Relevance
“…However, it is worth noting that in other non-western cultures mothers and fathers may have different roles in child adjustment and thus rGE may act differently as compared to western culture (Atzaba-Poria & Pike, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that in other non-western cultures mothers and fathers may have different roles in child adjustment and thus rGE may act differently as compared to western culture (Atzaba-Poria & Pike, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we acknowledge that we must draw our conclusions with caution. Still, other studies have found that children's perceptions of parents' behaviors can be meaningfully related to data provided by other reporters regarding family context or social adjustment (e.g., Atzaba-Poria & Pike, 2008;Gaylord, Kitzmann, & Coleman, 2003). Given the promise of our findings, we believe that it would be profitable to invest in future studies that include measures obtained from both parents and children, and that examine prospective relations among parents' behavior, children's interpretations of their behavior, and children's adjustment.…”
Section: Downloaded By [Simon Fraser University] At 16:19 20 Novembermentioning
confidence: 97%
“…First, there has been slow but steady progress towards identifying specific sources of non-shared environment associated with outcomes. Recent research examines possible contextual moderators of the links between non-shared experiences and outcomes 50 . Second, non-shared experiences outside the family are increasingly targets for these investigations 38 , 51 .…”
Section: Children In the Same Family Are Very Different But Why?mentioning
confidence: 99%